Experimental investigation on thermal properties of carbon nanotubes/zinc silicate composites prepared by powder processing - Chan, Kar Fei; Zaid, Mohd Hafiz Mohd; Mamat, Md Shuhazlly; Tanemura, Masaki; Liza, Shahira; Miyazaki, Hidetoshi; Maruyama, Takahiro; Sako, Katsuya; Sharma, Kamal Prasad; Osman, Nurul Huda; Sa'at, Nor Kamilah; Mazlan, Hazeem Ikhwan; et al. (Elsevier, 2023)
Carbon nanotubes (CNTs) as fillers in ceramic matrix composites have been widely explored to enhance the thermal properties due to its excellent thermal transport mechanism. Zinc silicate (ZS) is a crystalline ceramic with good fluorescence properties but low thermal diffusivity and effusivity. The introduction of CNTs into ZS is a good approach to improve the thermal transport parameters of the ceramic. Carbon nanotubes/zinc silicate (CNTs/ZS) composites with various CNTs mass fractions, ranging from 0 to 3.0 wt%, were fabricated using a combination of powder processing and pressureless sintering. The measured surface hardness, alternating current (AC) conductivity and thermal diffusivity of CNTs-free ZS composites are 285 HV, 2.31 × 10−7 Sm−1, and 0.25 mm2s−1, respectively. Paradoxically, the composite's surface hardness and thermal diffusivity decreased by 90.3 % and 72.1 %, respectively, when 3.0 wt% CNTs were added, while the AC conductivity increased by 105 times. The reduced bulk density and the high degree of phonon scattering in grain boundaries led to a reduction in surface hardness and thermal diffusivity. In addition, the micro-morphology observations revealed that the CNTs aggregation rate increased proportionally with the CNTs mass fraction. The CNTs aggregation formed a soft phase at the composite's surface and a phonon scattering site, which further degraded the material's mechanical and thermal properties. The enhanced AC conductivity of the composites was attributable to the introduction of an efficient free electron flow path formed by the CNTs network. The combination technique of powder processing and pressureless sintering provided a fabrication route to prepare the CNTs/ZS composite with minimal complexity and expense. Through this fabrication method, the results allowed the CNTs-ceramic research path to be navigated in the better direction and served the scientific community in the development of micro-optoelectronic and passive heat sinks.